Pengaruh Profitabilitas, Financial Leverage dan Umur Perusahaan Terhadap Income Smoothing Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di BEI Periode 2018-2022 - Cindy Kurnia Rahim; Novera Martilova (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out and analyze how much influence Profitability, Financial Leverage and Company Age have on Income Smoothing in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX for the 2018-2022 Period. This type of research is quantitative research, the type of data is secondary data which can be accessed via the official website of the Indonesian Stock Exchange (www.idx.co.id). The sampling technique used in this research was the Purposive Sampling method with a total sample of 33 companies. Data analysis techniques use descriptive statistical tests, classical assumption tests, coefficient of determination tests and hypothesis tests. The results of this research partially show that the Profitability variable has no significant effect on Income Smoothing as evidenced by the results of the t count < t table test of 1.763 > 2.05553. Financial Leverage has a significant effect on Income Smoothing as evidenced by the t test results > t table of 2.868 < 2.05553. Company age does not have a significant effect on Income Smoothing as evidenced by the results of the t test < t table of 0.207 > 2.05553. Profitability, Financial Leverage and Company Age simultaneously have a significant effect on Income Smoothing as evidenced by the results of the f test which shows a significance value of 0.003 < 0.05, meaning that Ha is accepted.